Pollen morphology in Brazilian species of Gloxiniinae (Gesneriaceae): variation in apertures and pattern of ornamentation - de Souza, Cintia N. [UNESP]; de Araujo, Andréa O.; Chautems, Alain; da Cruz-Barros, Maria A. V.; Gasparino, Eduardo C. [UNESP] (Springer Nature, 2018)
Gloxiniinae comprises herbs and subshrubs usually growing on rocky outcrops, rocky fields or gallery forests. For Gesneriaceae in some cases variations in pollen morphology allow the differentiation of genera and species. We studied the pollen grains of ten Brazilian species of Gloxiniinae (Gesneriaceae), including the genera Chautemsia, Gloxinia, Goyazia, Mandirola and Seemannia with the purposes of describing the pollen morphology of these genera, and contributing to the taxonomic characterization of the group and a better delimitation of genera and species of Gesneriaceae. The pollen grains were acetolyzed, measured, photographed and described qualitatively. Quantitative data were analyzed through descriptive and multivariate statistics. Non-acetolyzed pollen grains were observed in SEM and TEM in order to provide more details of the ornamentation and the structure of the exine. The analyzed species differ as to the pollen amb, shape, length, width and ends of colpi, presence or absence of margo, type of endoaperture and exine ornamentation. We found circular, subcircular and subtriangular amb, oblate spheroidal and subprolate shape, long or very long colpi, narrow, wide or very wide, with or without margo, lalongate or lolongate endoaperture in microreticulate or reticulate pollen grains. The reticulate ornamentation appears in the Gloxinia species’ pollen grains, and lolongate endoapertures represent the pattern for the subtribe pollen grains except in Chautemsia. The pollen grain metrics examined by principal component analysis allow generic distinction. We conclude that qualitative and quantitative pollen data help to delimit the genera and species of Gloxiniinae.
Keywords: Endoaperture; Exine; Gesnerieae; Multivariate analysis; Palynotaxonomy; Pollen grains